Stable isotopes and the seasonality of the Oronsay middens - Richards, M. P.
Research on six late Mesolithic shell middens on the small Hebridean island of Oronsay address questions of permanent and seasonal occupation. Stable isotope analysis of human bones shows marine resources providing the majority of protein, supporting year-round occupation of Oronsay. One individual, however, demonstrated a mixed diet of marine and terrestrial protein, suggesting seasonal visits and different patterns of site occupation.